ORGANIC FARMING PRACTICES IN SIKKIM SCHOOLS: A PATH TO EDUCATION FOR SUSTAINABLE DEVELOPMENT - Syangbo, Genevive (International Journal of Research -GRANTHAALAYAH, 2019)
The National Curriculum Framework 2005 under its guiding principles includes the need to make ‘children sensitive to the environment and the need for its protection’ while living in harmony within oneself and with one’s natural and social environment as an important curricular concern (p6). Education for Sustainable Development (ESD) with its emphasis on fostering of ‘competencies that enable students to find sustainable solutions to demanding issues and prevent conflicts’ in their world is seen as a process towards such a goal. In this regard, Sikkim’s initiative towards achieving this broader aim of education has been an ongoing process in schools of Sikkim. This paper presents, from an educational perspective, integration of Education for Sustainable Development (ESD) through practice of Organic farming in government schools in Sikkim. This enables the objective of embedding ESD goals aiming towards development of competencies among learners for sustainable living. The paper also focuses on how the concept of organic farming and green schools has been incorporated into the school curriculum. The process involving schools and the community to work together through a participatory and collaborative approach is enabling all stakeholders of school education to understand and practice the principles of sustainable development with available resources within their communities.